2019
DOI: 10.1002/cncr.32629
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell transplantation from a haploidentical donor versus a genoidentical sister for adult male patients with acute myelogenous leukemia in first remission: A retrospective study from the acute leukemia working party of the European Society for Blood and Marrow Transplantation

Abstract: Background In adult patients with acute myeloid leukemia (AML), a matched sibling donor (MSD) is considered the first choice for an allogeneic transplantation. However, a female donor for a male recipient is a poor prognostic factor. The authors compared haploidentical (HAPLO) donors with female MSDs. Methods In total, 834 men underwent allogenic transplantation from a female MSD, and 232 men underwent allogenic transplantation from a HAPLO donor. Of these, 86% of HAPLO recipients and 3% of MSD recipients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
3
5
0
Order By: Relevance
“…Additionally, different outcomes were not found among the MSD, MUD, and HID transplant subgroups, although the sample sizes were limited. This agrees with results from recent studies, which have also indicated that clinical outcomes for HID are equivalent to MSD and MUD transplantation [ 39 42 ]. Therefore, consolidation chemotherapy and auto-HSCT could be considered a valuable alternative after induction therapy, which may be preferred for patients with IR-AML and MRD3 negativity in the absence of a suitably matched donor.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, different outcomes were not found among the MSD, MUD, and HID transplant subgroups, although the sample sizes were limited. This agrees with results from recent studies, which have also indicated that clinical outcomes for HID are equivalent to MSD and MUD transplantation [ 39 42 ]. Therefore, consolidation chemotherapy and auto-HSCT could be considered a valuable alternative after induction therapy, which may be preferred for patients with IR-AML and MRD3 negativity in the absence of a suitably matched donor.…”
Section: Discussionsupporting
confidence: 92%
“…Data from our retrospective analysis showed that patients receiving HSCT from an MSD or HSD can achieve equivalent 5-year OS and DFS; however, after controlling for high-risk patients, a superior GVL effect was observed in high-risk patients undergoing HSD-HSCT with lower relapse and higher DFS rates compared to patients undergoing MSD-HSCTs. The priority use of T-cell-replete HID-HSCT with ATG or PT-Cy in high-risk patients has been reported by our group and other groups 1,23,36 ; however, according to our study no advantage of HID-HSCTs was observed in intermediate/standard-risk patients for HSDs or HPDs. However, it is also worth noting that the follow-up after the new donor selection strategy to our case is short and needs longer follow-up and a larger number and more homogeneous of patient population to confirm the efficiency of the new donor selection strategy.…”
Section: Discussionsupporting
confidence: 49%
“…A retrospective study from the EBMT involving 1066 male adult patients with de novo AML undergoing a first allo‐HSCT in CR1 using a female MSD or a T‐replete haploidentical male or female donor, suggested that in men with intermediate‐risk AML, allo‐HSCT from a sister MSD or a haploidentical donor produces similar GRFS. In men who have high‐risk AML, a haploidentical donor may be a better choice 23 . To date, there were four published studies involving donor options for old patients receiving allo‐HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GRFS survival was comparable. However, in high-risk AML patients, haploidentical recipients had lower rates of relapse as well as superior GRFS, LFS, and OS [ 65 ].…”
Section: Donor Selection From Among Haplotypesmentioning
confidence: 99%